Consideration of Ketogenic Metabolic Therapy as a Complementary or Alternative Approach for Managing Breast Cancer - Seyfried, Thomas N.; Mukherjee, Purna; Iyikesici, Mehmet S.; Slocum, Abdul; Kalamian, Miriam; Spinosa, Jean-Pierre; Chinopoulos, Christos (Frontiers in Nutrition, 2020)
Breast cancer remains as a significant cause of morbidity and mortality in women. Ultrastructural and biochemical evidence from breast biopsy tissue and cancer cells shows mitochondrial abnormalities that are incompatible with energy production through oxidative phosphorylation (OxPhos). Consequently, breast cancer, like most cancers, will become more reliant on substrate level phosphorylation (fermentation) than on oxidative phosphorylation (OxPhos) for growth consistent with the mitochondrial metabolic theory of cancer. Glucose and glutamine are the prime fermentable fuels that underlie therapy resistance and drive breast cancer growth through substrate level phosphorylation (SLP) in both the cytoplasm (Warburg Effect) and the mitochondria (Warburg Q-Effect), respectively. Emerging evidence indicates that ketogenic metabolic therapy (KMT) can reduce glucose availability to tumor cells while simultaneously elevating ketone bodies, a non-fermentable metabolic fuel. It is suggested that KMT would be most effective when used together with glutamine targeting. Information is reviewed for suggesting how KMT could reduce systemic inflammation and target tumor cells without causing damage to normal cells. Implementation of KMT in the clinic could improve progression free and overall survival for patients with breast cancer.